Use of intrarradicular pins in primary teeth: case report of one year of accompanying - Rafaela Cavalcanti AMARAL; Ivana Aguiar FERREIRA; Soraya Cristhina de Souza CAMPELLO; Ana Flávia Bissoto CALVO; Tamara Kerber TEDESCO; José Carlos Petorossi IMPARATO (Faculdade São Leopoldo Mandic, 2019)
Primary teeth have an important role in the growth and development of the child, besides being important for the good performance of masticatory function, phonation, occlusion and aesthetics, are the best space maintainers and eruption guide for the permanent successor. For anterior region, there are different alternatives of rehabilitation treatment, however, it is up to the professional to choose the best option. To present a therapeutic management of upper incisors affected by carious lesion with intrarradicular pin in early childhood. Case report: male patient, with 2 years and 7 months of age and significant loss of dental structure at an early stage. In the impossibility of performing direct restoration, we opted for the rehabilitation with the use of glass fiber pins for intraradicular reinforcement and composite resin restorations in order to restore shape, function and aesthetics. The use of fiberglass intra-radicular pins associated with direct restoration of composite resin is a recommended technique for the reconstruction of anterior teeth with great destruction.